Antibacterial Activity of Zingiber officinale Rhizome - Yusuf Alkandahri, Maulana; Hari Kusumati, Anggun; Fikayuniar, Lia (International Journal of Psychosocial Rehabilitation, 2020)
Background: The aim of this study was to determine the antibacterial activity and phyto-chemical screening of the Zingiber officinale ethanol extract. Fresh rhizomes of Z. officinale (Ginger) are collected from Manoko Plantation in Bandung, West Java, Indonesia. Methods: Antibacterial activity was determined using the well diffusion method while phytochemical screening was performed to determine the phytochemical composition of the ginger rhizome. Results: Results of phytochemical screening revealed phenolic compounds, alkaloids, flavonoids, tannins, and terpenoids. Results for bioassay presented variations in the biological activity of the extract. The extract showed antibacterial activity against all bacteria tested with inhibition diameter zones ranging from 2.67 to 12.47 mm mm. The highest zone was observed in Staphylococcus aureus at 400 mg/ml while the smallest inhibition zone was observed in Pseudomonas aeruginosa at 100 mg/ml. Conclusion: Our research proves that Z. officinale rhizome extract has the ability to inhibit bacterial growth. This shows that Z. officinale can potentially be used to develop new agents for combat bacteria. However, further studies are needed to explain the mechanism behind these effects.